Pathological Impact of the Interaction of NO and CO with Mitochondria in Critical Care Diseases - Duvigneau, J. Catharina; Kozlov, Andrey V. (Frontiers in Medicine, 2017)
The outcome of patients with critical care diseases (CCD) such as sepsis, hemorrhagic shock, or trauma is often associated with mitochondrial dysfunction. In turn mitochondrial dysfunction is frequently induced upon interaction with nitric oxide (NO) and carbon monoxide (CO), two gaseous messengers formed in the body by NO synthase (NOS) and heme oxygenase (HO), respectively. Both, NOS and HO are upregulated in the majority of CCD. A multitude of factors that are associated with the pathology of CCD exert a potential to interfere with mitochondrial function or the effects of the gaseous messengers. From these, four major factors can be identified that directly influence the effects of NO and CO on mitochondria and which are defined by, (i) local concentration of NO and/or CO, (ii) tissue oxygenation, (iii) redox status of cells in terms of facilitating or inhibiting reactive oxygen species formation and (iv) the degree of tissue acidosis. The combination of these four factors in specific pathological situations defines whether effects of NO and CO are beneficial or deleterious.